Use of eHealth tools by primary care physicians according to the provided healthcare in the Czech Republic - Eva Ardielli (Scientific Papers of the University of Pardubice, Series D: Faculty of Economics and Administration, 2021)
One of the main goals at the European level is that healthcare systems must be accessible but at the same time cost-effective and sustainable in the long term. The implementation of eHealth is one way to contribute to this goal. The presented paper is focused on the evaluation of the usage of eHealth tools in medical clinics in the Czech Republic. eHealth development is an important tool of health policy in the Czech Republic and an important goal of Czech health care reforms, as it has the potential to improve the availability of healthcare and to increase its quality and effectiveness. The aim of the paper is to evaluate the use of eHealth tools adopted in primary care medical clinics according to the type of provided healthcare and according to the NUTS 3 regions in the Czech Republic. The evaluation is performed by application of the multicriteria decision-making methods. The research results indicate that the usage of eHealth tools in medical clinics vary significantly depending on the type of healthcare provided and also in individual NUTS 3 regions. It was found that the eHealth tools are used to the greatest extent in gynecological clinics and to a lesser extent in dentist clinics. Based on the comparison of the eHealth Index, the ranking of the regions in the Czech Republic was determined from the most successful to the least successful in terms of the use of eHealth tools in medical clinics.
Keywords: H75; I11; I18; 330; Czech Republic; eHealth; ICT; MCDM methods; outpatient healthcare; TOPSIS